FEATURES OF FORMATION OF COALITION GOVERNMENTS IN POST-SOCIALIST COUNTRIES OF CENTRAL EUROPE: EXPERIENCE FOR UKRAINE - Sukhenko V. V. (Pressing Problems of Public Administration, 2016)
The article investigates foreign experience of coalition government of ces formation in terms of twopost-socialist countries of Central Europe - Poland and the Czech Republic. It analyzes the conditionsand processes that accompanied the creation of a coalition government of these countries, the mainproblems concerning the formation and functioning of coalition governments in Ukraine and outlinedfurther priorities solutions.